PS-B08-5: EFFECT OF HIGH SALT INTAKE ON THE SODIUM CONTENT OF EACH BONE IN RATS. (January 2023) - Munesada, Mahiro; Kitada, Kento; Kidoguchi, Satoshi; Nakano, Daisuke; Nishiyama, Akira
Abstract : Objective: It has been reported that salt intake affects sodium content at the tissue level. Salt intake alters bone sodium content, which shifts the balance of osteoblasts and osteoclasts population and thereby affects bone density. However, it remains to be clarified whether there are site-specific changes in bone sodium content. In the present study, we examined the effect of high salt intake on the sodium content of each bone in normal rats. Design and method: Male Sprague Dawley rats (9 weeks old) were fed with a 0.2% normal salt diet with tap water to drink or a 4% high salt diet with 0.9% NaCl water to drink for 3 weeks. Each bone sodium content was measured by the ashing-flame photometer method. Results: High salt intake significantly increased total bone sodium content. Compared with normal salt group, high salt group exhibited a significant increase in the bone sodium content of skulls, ribs, or tailbones. On the other hand, high salt intake did not alter bone sodium content in the scapula, pelvis, vertebrae, and limb bones. Conclusions: There is a site-specificity of bone sodium accumulation with high salt intake. These findings suggest that each bone has local sodium regulation independently of whole bones and that bones could be separated into whether or not to store sodium. It may be necessary to evaluate the sodium content of each bone in various pathological models, rather than a simple measurement of the total bone sodium content.